Análise da gestão de cooperativas rurais tradicionais e populares : estudo de casos na Cocamar e Copavi - Chiariello, Caio Luis (2008)
Led back to the center of the politician debate since 1970 s, the liberal speech affirms that the economic development proportionated by the global market is enough to solve workers unemployment. In this context, liberals defend that the association of workers in cooperatives is functional to the capitalism, brightening up social effects of the cyclical crises of production, losing its function when of the increase of the production, and soon of the job. So, cooperatives would appropriate of the technical instruments of management from typically capitalist companies and would evolve to become capital valuation spaces. In the Brazilian case, this conception bases the theoretical reflection about the necessity of the traditional agricultural cooperatives to seem its management in the great participant companies of the agribusiness, adhering to the postulates of economic rationality, searching for profit. This text presents the case study on a traditional agricultural cooperative with this profile, the Cooperative COCAMAR, identificated with capital companies. On the other hand, in Brazil, since 1990 s, many workers started organizing themselves democratically in solidary economic enterprises. They ve searched for job and struggled with unemployment, intending the continuity of their activities, subordinating the economic rationality to the social rationality. Popular cooperatives are some of these enterprises, originated from social movements of resistance, worried in offering better conditions of life to the associates. One of the main challenges of these popular cooperatives is the adoption of management tools that make possible greater effectiveness in the production and permit their permanence in the market, but not compromising its solidary principles. This text also presents a case study done on the Cooperative - COPAVI, each was founded by no land workers of MST. Through the empirical inquiry, we ve analyzed some management elements: the collective property of the land and the means of production; the access to the credit under differentiated conditions; the search for an effective internal democracy and organization of work under the self management, taken as fundamental to COPAVI exerts its activities into the capitalism, but not omitting its solidary principles and its character of social movement.